2006
DOI: 10.1051/0004-6361:20054045
|View full text |Cite
|
Sign up to set email alerts
|

Circumnuclear star-forming activities along the Hubble sequence

Abstract: In order to study circumnuclear star-forming activity along the Hubble sequence, we cross-correlated the Sloan Digital Sky Survey Data Release 2 (SDSS DR2) with the Third Reference Catalog of Bright Galaxies (RC3) to derive a large sample of 1015 galaxies with both morphological and spectral information. Among these, 385 sources are classified as star-forming galaxies, and the SDSS fibre covered the circumnuclear regions (0.2−2.0 kpc). By using the spectral synthesis method to remove the contribution from the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 72 publications
(118 reference statements)
5
15
1
Order By: Relevance
“…Furthermore, it prevents us from estimating the influence of diffuse ionized gas, which can boost the Balmer emission (Blanc et al 2009), and therefore, we might overestimate the calculated SFR. Scaling the Calzetti (2012) SFR of the central SF-region to an area of 1 kpc 2 yields a SFR-density of Σ SFR ≈ 0.06 M yr −1 kpc −2 , which is lower than the median value of 0.2 M yr −1 kpc −2 for circumnuclear (0.2 kpc ≤ 2 kpc) SF in galaxies that are the same Hubble type and that are located at roughly the same distance (z = 0.00344−0.0344) (Shi et al 2006) (see also Valencia-S. et al 2012).…”
Section: Hii Regionsmentioning
confidence: 64%
“…Furthermore, it prevents us from estimating the influence of diffuse ionized gas, which can boost the Balmer emission (Blanc et al 2009), and therefore, we might overestimate the calculated SFR. Scaling the Calzetti (2012) SFR of the central SF-region to an area of 1 kpc 2 yields a SFR-density of Σ SFR ≈ 0.06 M yr −1 kpc −2 , which is lower than the median value of 0.2 M yr −1 kpc −2 for circumnuclear (0.2 kpc ≤ 2 kpc) SF in galaxies that are the same Hubble type and that are located at roughly the same distance (z = 0.00344−0.0344) (Shi et al 2006) (see also Valencia-S. et al 2012).…”
Section: Hii Regionsmentioning
confidence: 64%
“…After the gas density becomes supercritical in the central parts, the next step is to trigger circumnuclear star formation (Sheth et al 2005); (pseudo)bulges also grow during this process (Kormendy & Kennicutt 2004). These processes have been proven by a large number of observations (e.g., Knapen et al 2006;Shi et al 2006;Gadotti 2010) and simulations (e.g., Athanassoula et al 2009). Gadotti & dos Anjos (2001) also studied the broadband UBV color profiles for 257 Sbc barred and nonbarred galaxies and found that the bulges of barred galaxies are bluer than others, indicating an increase in the star formation rate (SFR) in the central regions of these objects.…”
Section: Introductionmentioning
confidence: 88%
“…Theoretically, stellar bars can concentrate a substantial fraction of disk gas in small galactocentric radii as a result of star formation (Kormendy & Kennicutt 2004). Observations have also found that, on average, galaxies with stellar bars show higher central SFRs than unbarred galaxies (e.g., Kormendy & Fisher 2005;Fisher 2006;Shi et al 2006), and the star formation in circumnuclear regions of spiral galaxies is more dependent on stellar bars than that in their outer disks (Kennicutt 1998). Using mid-IR color to trace star formation activity, Roussel et al (2001) also found that the color distributions of strong barred galaxies show 15 μm excess, which is absent from weakly barred or unbarred galaxies.…”
Section: Bar-driven Star Formation and Galactic Evolutionmentioning
confidence: 99%
“…The galaxy is clearly a spiral". Shi et al (2006) described it as SAa with emission line spectra. The blue integral colours (U − B = −0.04 and B − V = 0.76) of the galaxy are typical for Sb spirals (e.g., Huchra 1977).…”
Section: The Morphological Classificationmentioning
confidence: 99%